Brain metastases from rectal cancer – case report - Litak, Jakub; Kamiński, Maciej; Budny, Agnieszka; Grochowski, Cezary; Litak, Joanna; Kamieniak, Piotr (Journal of Education, Health and Sport, 2017)
Colorectal origin of brain metastases (BM) are relatively rare in oncological practice. Represent 0,6% to 3,2% of all brain metastatic lesions with median survival time of 2.8–5.4 months. Only very few patients survive more than 1 year. Metastases spread to the brain reflecting the vascular anatomy. Colorectal metastases appear early and more frequently in pulmon and liver. BM use to be called late metastases. Thanks to highier availability of diagnostic methods as a CT or MRI detectability of BM raised significantly. Early diagnosis and treatment of BM provide proper quality of life for patient , in addition to adequate control of prime colorectal cancer.